DETERMINANTS OF UTILIZATION OF MATERNAL HEALTH CARE SERVICES IN TANA RIVER COUNTY, KENYA - Badru, Abdullatif; Njoroge, Kezia; Oluoch, Musa (Journal of Health, Medicine and Nursing, 2022)
Purpose: The main purpose of this study was to determine factors influencing utilization of delivery services by Women of Reproductive age in Tana River County Methodology: The study was cross-sectional in design. The target population included all women of reproductive age (14-49 years) in Kipini location. The study population consisted of women of reproductive age who had delivered. A structured questionnaire was used as the primary instrument of data collection during interviews of the consenting women of reproductive age. The sampling techniques used involved a combination of cluster sampling, proportionate, systematic sampling and simple random sampling. Data analysis was done using the SPSS. Authorization from the Kenya Methodist University ethical committee was sought prior to data collection Findings: A total of 335 (95.7%) questionnaires were filled and returned. Majority of the respondents were married, with a primary level of education, occupation being farmers. Majority of the women had their last delivery in a hospitals (80%), with most of the delivery happened in private facilities (77.6%). From the findings, cultural and cost factors had a negative relationship to the utilization of delivery services by women of the reproductive age. However, access and socio-demographic factors had a positive and significant relationship to the utilization of delivery services by women of the reproductive in Tana River County. Unique Contribution to Theory, Practice and Policy recommendation: The study recommended skilled attendants to allow some safe cultural and religious practices during delivery so as to encourage the utilization of delivery services. It also recommended that the county government enforce the free maternity policies by making sure that no hidden or additional fee is charged to the women during delivery. The government should increase the number of permanent and mobile health facilities In Tana River County so that every women (including normadic population) to have access to delivery services